NOVEL BENZOTHIAZOLE-ISATIN HYBRIDS: MICROWAVE SYNTHESIS AND COMPUTATIONAL INSIGHTS AGAINST MULTIDRUG-RESISTANT TUBERCULOSIS - THIRUMALA ROOPESH G; GEETHAVANI M (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objective: Multidrug-resistant tuberculosis (MDR-TB) is the outcome of Mycobacterium tuberculosis developing resistance to at least isoniazid or rifampicin, the two most effective first-line anti-TB drugs. A major worldwide health concern, this resistance makes treatment regimens more challenging and necessitates the development of new therapeutic agents and medication delivery methods. A class of heterocyclic chemicals called benzothiazole derivatives is well-known for its many biological actions, including antibacterial, antitubercular, anticancer, & anti-inflammatory properties. Recent studies have shown that these compounds hold promise in the use of both laboratory and computer-based techniques to create novel medications, particularly against drug-resistant illnesses. Methods: In the current research, several new benzothiazole-based molecules were synthesized and evaluated for their antitubercular potential using both experimental testing and molecular modelling. Out of the synthesized compounds, Histidine, Serine, Valine, Phenylalanine and Tyrosine derivatives showed notable activity against Mycobacterium tuberculosis at a concentration of 3.12 µg/ml, which is similar to that of pyrazinamide, a common medication. While compound IG showed decreased activity at 12.5 µg/ml, compounds such as tryptophan derivatives, proline, glutamic acid, and cysteine showed considerable activity at 6.25 µg/ml. Mass spectrometry and FTIR were used to verify the purity and chemical structure of every produced molecule. Standard protocols recorded their physical characteristics, such as solubility, melting point, or Rf values. To conduct molecular docking investigations, AutoDock 4.2.6 was used, and PyRx software against the Protein Data Bank ID: 2JA2 protein target. Results: The compound (ITRYPT)Tryptophan Derivative showed the strongest binding energy of –8.8 kcal/mol, better than the standard drugs and the co-crystal ligand Acetate ion (ACT) (–5.3 kcal/mol). Other active compounds such as (IH) Histidine, (IP) Proline, (IS) serine, and (IAA) Aspartic acid derivatives also showed strong binding energies between -8.8 and -8.3 kcal/mol. In-depth interaction analyses showed that these substances created pi-cation interactions, π–π stacking, & hydrogen bonding. With key amino acids like Trp67, Arg271, Asp272 in the protein’s active site. Toxicity was predicted using the PROTOX-3 server, and the results indicated that the compounds were within acceptable safety limits. Conclusion: Overall, Tryptophan derivative and other active derivatives have shown encouraging results and may be considered for further biological studies and structure-activity relationship (SAR) analysis to develop effective antitubercular agents.